O18.6 Prenatal care entry among pregnant women with syphilis who use methamphetamines: a key to congenital syphilis prevention. (14th July 2019) - Plotzker, Rosalyn; Burghardt, Nicole; Bauer, Heidi
Abstract : Background: In California, congenital syphilis (CS) increased for the fifth consecutive year in 2017, and contributed one third of CS cases in the United States. In response, state and local STD programs implemented CS prevention strategies. A CS Prevention Cascade monitors impact, assesses prenatal care (PNC) gaps, and estimates CS cases averted. Methods: This analysis used 2017 California Project Area surveillance data for women diagnosed with syphilis during pregnancy or at delivery. Cases were assessed for the following, each met≥30 days prior to delivery: documented PNC, syphilis screening, treatment initiation, and treatment adequacy by stage. Data for each cascade bar included women counted in the preceding bar(s). The final bar represented the CS Prevention Ratio (CSPR) – the proportion of pregnant syphilis cases who did not deliver a CS infant. This cascade was then stratified by MU, defined as having either self-reported use upon interview or positive urine toxicology in pregnancy or at delivery. Three groups were identified: Non-MU (NMU); Positive-MU (PMU); Not interviewed (NI). A post-hoc stratified cascade included only pregnant syphilis cases with documented PNC, to explore how MU might impact CS case aversion once PNC is initiated. Results: 616 women were included; 239/118/259 were NMU/PMU/NI respectively. Within these groups 95%/86%/71% met PNC criteria, 89%/81%/66% received syphilis screening, 84%/75%/63% initiated treatment, 82%/73%/61% met treatment adequacy, and CSPR were 79%/69%/59% (p<0.001). However, when considering only those with documented PNC(n=226/101/183): 94%/95%/94% received syphilis screening, 88%/88%/89% initiated treatment, 87%/85%/87% met treatment adequacy, and CSPR were 84%/81%/84% (p=0.84). Conclusion: Compared to NMU, PMU and NI were associated with a decreased CSPR. When considering only those with documented PNC, significant differences between groups were not observed, suggesting PNC entry may be a key intervention for CS prevention. Disclosure: No significant relationships.